Marriage Financing in Islamic Law: A Maqasid al-Shariah Analysis of Wahbah al-Zuhaili’s Thought - Iswadi Muhammad Yazid; Masduki Masduki; Mawardi Mawardi (Hukum Keluarga Islam IAIN LANGSA, 2025)
Islam regards marriage as an act of worship that guides believers toward a balance between simplicity and moral responsibility. However, in modern social practice, there is a growing gap between the Islamic principle of simplicity and the rising costs of marriage, such as expensive dowries and lavish wedding ceremonies, which shift the values of maqasid al-shariah toward a materialistic culture. This study aims to analyze Wahbah al-Zuhaili’s thought on the allocation of marriage expenses from the perspective of maqasid al-shariah and its relevance to contemporary social practices. This research employs a qualitative library-based approach with descriptive-analytical methods. The primary sources include the works of Wahbah al-Zuhaili, particularly al-Fiqh al-Islami wa Adillatuhu, along with relevant classical fiqh literature and contemporary studies. Data were analyzed using thematic analysis to identify the legal principles underlying marriage financing within the framework of maqasid al-shariah. The findings reveal that Wahbah al-Zuhaili’s legal framework makes a significant contribution to the development of contemporary Islamic jurisprudence by integrating maqasid al-shariah into the discourse on marriage financing. His emphasis on simplicity, justice, and public welfare provides a practical direction for developing an efficient marriage system through community support, the role of zakat institutions, and state facilitation. These findings imply the formulation of social guidelines and religious policy recommendations aimed at reducing the economic burden of marriage without neglecting its spiritual values.